Isi dan Makna Puisi Kluwung Karya Soewardi Baroto Martono: Pendekatan Pragmatik - Febriani, Gabriela; Alfiah, Alfiah (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2023)
Javanese people or rather Javanese ethnic groups, culturally and anthropologically, are people who in their daily lives use the Javanese language with various kinds of dialects from generation to generation. According to Kodiran (1981: 322), the Javanese cultural area covers the entire central and eastern part of the island of Java. An example of a Javanese literary works are also still quite a lot. Geguritan is a literary creation in the form of poetry which is usually sung with a very melodious song (Pupuh). This study takes as an example a literary work of poetry entitled Kluwung by Soewardi Baroto Martono. To find this literary work, the author uses a pragmatic approach that views literary works as a means to convey certain goals to the reader. This study also aims to find out the content and meaning of everyday life in Soewardi Baroto Martono’s Kluwung poetry.